LEVEL OF FARMER PARTICIPATION IN THE UTILIZATION OF RICE PAPER WASTE AS A COMPOST: TINGKAT PARTISIPASI PETANI DALAM PEMANFAATAN LIMBAH JERAMI PADI SEBAGAI PUPUK KOMPOS - Achdiyat; Siti Fatimah Annisa (Politeknik Pembangunan Pertanian Bogor, 2022)
The population of Tambaksari District is only about 20% of farmers who use straw as compost, there is a need for farmer participation in dealing with agricultural waste issues, especially rice straw as compost fertilizer. This study is to: Describe the level of participation of the utilization of straw waste, and factors related to the level of participation of farmers. The activity was carried out in Tambaksari Subdistrict, Ciamis Regency, from April to July 2019. Determination of the sample was carried out randomly using the Slovin formula and obtained 55 respondents. The results of the study, the level of participation of farmers included in the category of